Evaluation of Pain Intensity Caused by Nickel-Titanium Archwires of Different Sizes in the First Stage of Fixed Orthodontic Treatment: A Double-Blind Randomized Clinical Trial - Aydin Sohrabi; Shabnam Tahamtan; Sana Seyed Shariatdoust; Ali Rafighi (Journal of Mashhad Dental School)
Background: Orthodontic treatment involves the use of archwires to apply force to teeth, which can cause pain and discomfort for the patient. Pain may be one of the most significant factors deterring patients from continuing orthodontic therapy. The aim of the present study was to comparatively assess pain induced by different-sized nickel-titanium archwires during the first stage of fixed orthodontic therapy.Methods and Materials: This double-blind randomized clinical trial included a total of 81 patients who received fixed orthodontic therapy. Patients were divided in to three equal groups according to the size of the utilized initial archwire (0.012, 0.014, and 0.016 inches). Perceived pain after archwire placement was evaluated using Visual Analogue Scale (VAS). Pain was assessed at three time points, immediately after bracket bonding (T1), 4 weeks (T2) and 8 weeks (T3) thereafter. Pain assessment at each time point was evaluated at four intervals- at placement, 3 hours, 24 hours, and 3 days after the placement of wire. The Repeated Measures ANOVA test was used to evaluate the effects of archwire size and time after placement on reported pain levels.Results: The results showed that the pain reported in the superelastic nickel-titanium archwires of 0.012, 0.014, and 0.016 inches did not differ significantly from each other during the bonding session, 4 weeks, and 8 weeks after that (with p values of 0.404, 0.181, and 0.800, respectively). In other words, the size of the archwire did not affect the amount of pain caused. However, the intensity of pain over time at each of the mentioned intervals differed significantly (with p values of <0.001, <0.001, and 0.012, respectively), initially increasing and then decreasing over the time period.Conclusion: Over an 8-week long follow-up period, the size of the arch wire does not affect the reported level of pain, but the intensity of pain varies over time and follows a non-linear pattern, increasing at the beginning of the time period and then decreasing.